An Environmental Ethics Review of the Moral Dilemma Faced by Colored Stone Miners on Kolbano Beach - VERA VELWYATI; IRENE LUDJI (Universitas PGRI Kanjuruhan Malang, 2026)
The moral dilemma of miners on Kolbano Beach, South Central Timor (Timor Tengah Selatan), East Nusa Tenggara (Nusa Tenggara Timur) arises when they must dig into the soil to extract colored stones to meet their economic needs, even though this activity harms the environment. If they stop mining, no other occupation offers a comparable income, which explains why mining continues to this day. This study aims to describe the factors behind the moral dilemma faced by colored stone miners on Kolbano Beach and to analyze this dilemma from the perspective of environmental ethics. The study employs a qualitative, narrative-descriptive approach. Drawing on Larry Rasmussen's environmental ethics and Sallie McFague's distributive justice, the study calls on humans to pursue a sustainable life for all of creation in the future. As moral beings who continuously interact with nature, miners hold a duty to love nature as they love themselves and to treat nature as a moral subject. Humans also need to take responsibility for their moral decisions toward all creation through critical moral reasoning, which builds the character of humility and supports justice for all creation.